SCIENTIFIC/THEORETIC APPROACHES TO INNOVATIVE MANAGEMENT (WITH TRANSPORT AS AN EXAMPLE) - O. N. Dounayev (Модернизация, инновация, развитие, 2016)
Innovative management is a type of interactive activities based on a system of direct and reverse links with innovative process, the object of the management. At present, the innovative management concept is in the research and development phase as a part of the strategic management concept; the former having not yet get separated from the latter. So far as development of the innovative concept for the transport industry is concerned, the classical, evolutionary, behavior-dependent, institutional, strategic and entrepreneurship-dependent approaches are of special importance in terms of organization of the management. Key values of the transport innovative management organization system are formulated.